2012
DOI: 10.5430/afr.v1n2p161
|View full text |Cite
|
Sign up to set email alerts
|

The Intervening Effect of Global Financial Condition on the Determinants of Bank Performance: Evidence from Nigeria

Abstract: The global financial crisis had devastating effect on both developed and developing economies. In Nigeria, the effect of the crisis swerve through the major sectors of the economy with the banking sector greatly affected. This study investigates the determinants of Nigerian banks' performance from 1999 to 2010 while taking into consideration the intervening effect of global financial condition. The data of the study, which were extracted from annual reports of the banks as well as various publications of Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
11
3
Order By: Relevance
“…Hashim, 2014). In Nigeria, the banking sector is an essential component of the Nigerian financial system; the banking sector accounts for about 90 percent of the total assets in the Nigerian financial system and about 60 percent of market capitalization in the Nigerian Stock Exchange (Alabede, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hashim, 2014). In Nigeria, the banking sector is an essential component of the Nigerian financial system; the banking sector accounts for about 90 percent of the total assets in the Nigerian financial system and about 60 percent of market capitalization in the Nigerian Stock Exchange (Alabede, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Similar vein, CBN established the Assets Management Corporation of Nigeria (AMCON) aimed at reducing the problem of liquidity in the banking sector. Subsequently, the number of deposit money banks (DMBs) operating in Nigeria reduced to 20 with 5,810 branches at the end of the fiscal year 2011 (Alabede, 2012).…”
Section: Bank Performancementioning
confidence: 99%
“…Das ( 2013) studied real GDP growth rate and inflation as supplementary variables in the analysis. Alabede (2012) concluded that in the presence of the effect of global financial condition, only assets quality and market concentrations are significant determinants of the Nigerian banks' performance. The study suggested reducing nonperforming assets and introducing a policy to encourage fair competition among the banks.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the analysis ROA was used as indicator of bank performance. The same variable was used by Alabede (2012) in his study for analyzing the effect of global financial conditions on the bank performance in Nigeria.…”
Section: Gdp (Growth Rate)mentioning
confidence: 99%